A comparison of the therapeutic effectiveness of gastrin neutralisation in two human gastric cancer models: relation to endocrine and autocrine/paracrine gastrin mediated growth. Issue 6 (1st December 1999) - Watson, S A; Morris, T M; Varro, A; Michaeli, D; Smith, A M
Abstract : BACKGROUND: Gastrin is a growth factor for established tumours. AIMS: To investigate the therapeutic effect of antibodies, raised against the Gastrimmune immunogen, which neutralise the glycine extended and carboxy amidated forms of gastrin 17 in two human gastric cancer models. METHODS: MGLVA1 cells (which have a gastrin autocrine/paracrine phenotype) and ST16 cells (which have an endocrine phenotype) were injected into the peritoneal cavity of SCID mice. Peritoneal tumours, ascites, and cachexia formation occurred, with the monitored endpoint being morbidity. RESULTS: In MGLVA1 cells, intravenous administration of antibodies raised against Gastrimmune increased the 50% median survived by 25% at three different initial cell seeding concentrations (1 × 10 6 –5 × 10 5 per mouse). In ST16 cells, the effect of Gastrimmune induced antibodies on time to morbidity was greatest at the lowest cell seeding concentration (5 × 10 5 cells/mouse) with the 50% median survival increased by 74% and overall survival achieved in 38% of the mice. CONCLUSIONS: Gastrimmune may have potential therapeutic benefit on gastrin sensitive gastric tumours and may interact with both endocrine and autocrine mediated growth pathways.